KUALITAS UDARA RUANG PERAWATAN PENYAKIT MENULAR DI RUMAH SAKIT PARU SURABAYA TAHUN 2016 - Imro’atul Mufidah; Erna Triastuti; Ernita Sari (Poltekkes Kemenkes Surabaya, 2016)
Infectious disease treatment rooms are places with a high risk of the transmission of diseases and nosocomial infections. Therefore, there is a need for good environmental quality, either in terms of air quality, and room construction condition, cleaning process and number of occupant density. The study was a descriptive study aimed at describing the air quality of infectious disease treatment rooms in Lung Hospital Surabaya in 2016. Data were collected by means of observations, interviews, measurements and calculation of the airborne bacterial index. CFU/m3Results showed that the airborne bacterial index of inpatient rooms was 1030 CFU/m and 2628 CFU/m3 for Dahlia Room 1, Dahlia Room 2 and Pear Room, respectively. Room temperature was 29.8°C, 30.5°C and 30.9C for Dahlia Room 1, Dahlia Room 2 and Pear Room, respectively. Room humidity was 69%, 65% and 65% for Dahlia Room 1, Dahlia Room 2 and Pear Room, respectively. Room air velocity was eligible for Dahlia Room 1 and Dahlia Room 2 at 0.49 m/s and 2 0.18 m/s respectively, but It was not so for Pear Room at 0.89 m/s. Room lighting was 62 lux, 26 lux and 81 lux for Dahlia Room 1, Dahlia Room 2 and Pear Room, respectively. In conclusion, the airborne bacterial index, temperature, humidity and lighting in Lung Hospital Surabaya in 2016 did not meet the requirements as defined in Decree of the Minister of Health No. 1204/Menkes/SK/X/2004 on Hospital Environmental Health Requirements. It iis recommended to improve the cleaning and maintenance process of those rooms in accordance with health procedures and to improve construction of the rooms which do not meet the requirements. Keywords : Room air quality, Hospital